Pengembangan Media Pembelajaran Iqra Berbasis Multimedia Menggunakan Metode ADDIE - Zulfikar, Zulfikar (Jurnal Tika, 2022)
The presence of information technology with its various products has made it easier for humans to access various information, including information regarding various knowledge. The development of technology that is so extensive makes access to this information very easy and fast. The learning model during the Covid-19 pandemic has changed from a face-to-face conventional learning model to an online learning model. The change in the learning model is the background for the development of learning media carried out in this study, where the goal is to develop multimedia-based Iqra learning media in an interesting and interactive way. The method used in this research is using Research and Development, and using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) method, where through this method an Iqra learning media application was developed starting from the needs analysis stage and determining the initial system specifications, designing the interface, menus and sub menus, implementing and evaluating the feasibility of the application before the application is launched or used in general. The results of this study are the application of multimedia-based Iqra learning media, complete with tutorials and how to pronounce the letters which were developed with the Adobe Flash tool and can be run on devices that support Adobe Flash Player. Based on the test results, this application is able to run well on devices with the Windows operating system, by running files with the .exe extension obtained through the compilation process of the entire Iqra learning media application development project file